2015
DOI: 10.1080/14680629.2015.1020847
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of snow melting pavement performance using measured thermal properties of graphite-modified asphalt mixture

Abstract: Chemical melting agents are traditional methods for snow-removing applications. Due to their adverse environmental impact, thermo-snow melting pavements with conductive fillers are becoming frequently used. In this study, the thermo-physical properties of graphite-modified asphalt mixtures (GMAM) and the sensitivity of snow melting pavements were investigated. The microstructure of GMAM was analysed at extremely high magnification to observe the distribution of conductive fillers in the mixture. Two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The asphalt binder, PG 64-22, was mixed with four different conductive filler contents, 5, 10, 15, 20 percent by volume of asphalt binder. Aggregate was preheated to the mixing temperature of 170 ∘ C. By proceeding the mixing method done by Park and Vo [6,8], there are two ways to add conductive fillers into the mixture and they have certain effects on the conduction of heat in the asphalt mixture. For the wet-mixing process, conductive filler was blended into the asphalt using a high-speed shear mixer and a hot plate.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The asphalt binder, PG 64-22, was mixed with four different conductive filler contents, 5, 10, 15, 20 percent by volume of asphalt binder. Aggregate was preheated to the mixing temperature of 170 ∘ C. By proceeding the mixing method done by Park and Vo [6,8], there are two ways to add conductive fillers into the mixture and they have certain effects on the conduction of heat in the asphalt mixture. For the wet-mixing process, conductive filler was blended into the asphalt using a high-speed shear mixer and a hot plate.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Mixed conductive fillers have remarkable advantages over single powder filler at the same total content with respect to the conductivity. Vo et al [8] investigated the potential of using graphite as conductive filler for snow melting pavements and recommended 15 percent graphite content, by volume of asphalt binder, in the mixture as a reasonable amount.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical snow removal faces difficulties when removing snow compaction and can easily cause surface damage. Although snow melting agents, such as sodium chloride, calcium chloride, and magnesium chloride, are better at removing snow and ice, they cause corrosion to vehicles and concrete structures [3,4]. Considering the defects of traditional snow melting and deicing methods, it is necessary to develop a new, efficient, and clean method for removing snow and ice.…”
Section: Introductionmentioning
confidence: 99%
“…Heating coil was laid and fixed on the top of the lower layer prior to placing the upper layer so that the coil was in between the two layers (see Figure 3(b)). The heating temperature was controlled from a controlling box connected with a power source to provide a constant heat of 60 ∘ C, which is adequate for the snow-melting purpose during winter, according to Vo et al [13]. Although this analysis was based on a quite simple model, the method was verified as an adequate predictor of pavement heating rates.…”
Section: Actual Test Modelingmentioning
confidence: 99%
“…Moreover, stiffness, dynamic modulus, and tensile strength of asphalt mixture are also enhanced with an addition of carbon fibers. Vo et al [13] investigated the thermal conductivity of asphalt pavement with an addition of graphite powder as a conductive filler. It was concluded that the time for snow-melting process could be shortened by increasing the amount of graphite content; about half amount of the time could be reduced with a 20 percent of graphite added.…”
Section: Introductionmentioning
confidence: 99%